The durability of paints on sand-lime brick walls considering water sorption and vapour permeability in a two-layer system - Miniotaitė, Rūta; Stankevičius, Vytautas (Journal of Civil Engineering and Management, 2003)
It is assumed that the proposed coatings are suitable for finishing selected surfaces. However, our research indicated that the provided specific physical-mechanical properties of the coatings may change in a new combination of “coating–substrate”. It was found while analysing the results of grouped paints investigations that specific nature of vapour permeability and absorption, the effect of opposition thereof, the expansion of destruction and expression of its symptoms were characteristic of each group. Physical-mechanical properties of constructions substrate and finishing layer can supplement one another or, quite contrary, stimulate destruction. Analytical review of the influence made by two parameters (vapour resistance and rain penetration) upon durability of paints of various structural origins indicated that usually rain-penetration influence was higher. However, while evaluating humidity of complete finished layer (paint + substrate) as a process: “rain penetration – moisture migration from the inside (drying) – vapour isolation of the coating as a barrier to drying process”, in case of film-forming paints the influence of vapour resistance is high too.First Published Online: 26 Jul 2012